2020
DOI: 10.3390/ani10071185
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Parameters and Genome-Wide Association Studies for Anti-Müllerian Hormone Levels and Antral Follicle Populations Measured After Estrus Synchronization in Nellore Cattle

Abstract: Reproductive efficiency plays a major role in the long-term sustainability of livestock industries and can be improved through genetic and genomic selection. This study aimed to estimate genetic parameters (heritability and genetic correlation) and identify genomic regions and candidate genes associated with anti-Müllerian hormone levels (AMH) and antral follicle populations measured after estrous synchronization (AFP) in Nellore cattle. The datasets included phenotypic records for 1099 and 289 Nellore females… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 95 publications
0
15
0
Order By: Relevance
“…The increase in follicular size increases the AMH level. The dynamic expression pattern marks an AMH to be a potential endocrine marker to the size of ovarian pool, to improve reproduction rates and for the selection of better oocyte donor ( 9 , 13 , 21 , 26 ). In our present study, we report for the first time the complete coding sequence of AMH in Indian riverine buffalos and goats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The increase in follicular size increases the AMH level. The dynamic expression pattern marks an AMH to be a potential endocrine marker to the size of ovarian pool, to improve reproduction rates and for the selection of better oocyte donor ( 9 , 13 , 21 , 26 ). In our present study, we report for the first time the complete coding sequence of AMH in Indian riverine buffalos and goats.…”
Section: Discussionmentioning
confidence: 99%
“…Small follicles from healthy ovaries of Indian riverine buffaloes and goats were aspirated as described ( 25 , 26 ), and the pooled fluid containing granulosa cells were centrifuged at 500 × g for 5 min followed by washing twice with 1x PBS. RNA was isolated according to the manufactures protocol using TRI reagent (T9424, Sigma Aldrich, Merck, Darmstadt, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported the pedigree-based heritability of AMH as 0.43±0.07 and the genomic heritability of AMH as 0.36 ± 0.03 (Nawaz et al 2018). In another study, the estimation of genomic heritability of AMH in Nellore cattle (n=944) was reported as 0.28 ± 0.07 (Grigoletto et al 2020). Gobikrushanth et al (2018) indicated a high (0.46 ± 0.31) heritability estimate for AMH in Holstein cows (n=198).…”
Section: Genomic Heritability Of Amhmentioning
confidence: 96%
“…Genetic variation has been identified that is associated with AFC in beef heifers on chromosomes 2, 3, and 23 (Stegemiller et al, 2021). In Nellore cattle, regions of interest included chromosomes 1 and 26, which accounted for 6.2 and 7.3% of the total additive genetic variance, respectively (Grigoletto et al, 2020). For AGD, strong genetic markers are yet to be reported in cows (Gobikrushanth et al, 2019).…”
Section: Introductionmentioning
confidence: 99%